TMOD-03. A NOVEL MB GR3 TRANSGENIC MOUSE MODEL IS GENERATED BY MYCN AND P53 DEFECTS IN VENTRICULAR ZONE PROGENITORS. (1st June 2021) - Morcavallo, Alaide; Barker, Karen; Adachi, Toma; Boult, Jessica K R; Kwok, Colin; da Silva, Patricia Benites Goncalves; Okonechnikov, Konstantin; Hitchen, Luke; Robinson, Simon P; Clifford, Steven C; Pfister, Stefan M; Kawauchi, Daisuke; et al.
Abstract: Medulloblastoma (MB) represents the most common embryonal tumour of the Central Nervous System in childhood. MB occurs in the cerebellum and molecular features dictate the classification into four subgroups. Although Group3 (Gr3) MB tumours are dominated by primitive progenitor-like cells, the cells of origin remain unidentified. Gr3 MB is associated with relatively common MYC family member amplification and overexpression, often combined with p53 pathway defects at relapse. Molecularly stratified treatment is not yet available, causing Gr3 MB and its subsequent relapse to often represent an unstoppable progressive disease. The limited understanding of Gr3 tumorigenesis and targeted therapy development is also due to the lack of faithful in vivo models and consequently, their use in preclinical studies. We have now developed a new germline genetically engineered mouse model (GEMM), harbouring MYCN amplification in a p53 inactive background (tamoxifen-inducible p53 activation, Trp53ER TAM ). The purpose of the GEMM is to investigate the developmental significance of MYC aberration in putative Gr3 MB cells of origin and exploit it in preclinical studies. A LSL-MYCN-Luciferase strain was crossed with mice expressing Cre recombinase under the Blbp promoter and subsequently to Trp53ER TAM inducible mice. As result, the MYCN overexpression alone did not generate tumours, conversely to the combination of MYCN with p53 deregulation. Tumours arise exclusively in the hindbrain of homozygote mice, with a penetrance of 100% and a latency of ~135 days. Pathology report suggests tumours are Gr3 MB with large cell/anaplastic (LCA) histology. Preliminary transcriptional profiling data analysis reveals that tumours share molecular features with human counterparts, clustering with Gr3 MB. Ongoing analysis will explore the tumour cells of origin, followed by tumour progression alteration restoring p53 activity and blood-brain barrier integrity status. In conclusion, we have developed a MYCN/Trp53ER TAM Gr3 MB GEMM arising from ventricular zone progenitor cells and resembling human cancer characteristics.